2018
DOI: 10.21283/2376905x.8.128
|View full text |Cite
|
Sign up to set email alerts
|

¡Ya pué[h]! Perception of coda-/s/ weakening among L2 and heritage speakers in coastal Ecuador

Abstract: EN This investigation lies at the intersection of second language acquisition (SLA), sociophonetic variation, and speech perception.Specifically, it investigates the perception of coda /s/-aspiration (producing disco as [dih.ko]), a dialectal feature characteristic of Guayaquileño (coastal Ecuadorian) Spanish, among 14 young-adult English speakers who travel to Ecuador. The study investigates the participants' ability to perceive an aspirated variant as a legitimate /s/ over time as they are further exposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 34 publications
4
17
0
Order By: Relevance
“…Our results complement recent studies on SA and coda /s/ perception in Spanish, which have shown that, during a sojourn, learners became significantly more accurate at identifying [h] than they were prearrival (Escalante, 2018) and that learners who had studied in /s/-weakening regions were significantly more effective at identifying [h] as a production of /s/ than those had studied in /s/-conserving zones (Schmidt, 2018). The success of our advanced learners who had studied abroad in /s/-weakening regions, in conjunction with that of the phonetics group, lends credence to the hypothesis that learners who had first been instructed on language variation (e.g., sociophonetics, pragmatics) may benefit more from a sojourn abroad (Cohen & Shively, 2007; Lord, 2010; Shively, 2011).…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Our results complement recent studies on SA and coda /s/ perception in Spanish, which have shown that, during a sojourn, learners became significantly more accurate at identifying [h] than they were prearrival (Escalante, 2018) and that learners who had studied in /s/-weakening regions were significantly more effective at identifying [h] as a production of /s/ than those had studied in /s/-conserving zones (Schmidt, 2018). The success of our advanced learners who had studied abroad in /s/-weakening regions, in conjunction with that of the phonetics group, lends credence to the hypothesis that learners who had first been instructed on language variation (e.g., sociophonetics, pragmatics) may benefit more from a sojourn abroad (Cohen & Shively, 2007; Lord, 2010; Shively, 2011).…”
Section: Discussionsupporting
confidence: 90%
“…Before learners can link phonetic variation with social meaning, they must first learn to associate different variants with a single variable, and three recent studies explored how learners perceive the variants of coda /s/ (Del Saz, 2019; Escalante, 2018; Schmidt, 2018). These studies usually appeal to some combination of the aforementioned PAM-L2, SLM, and L2LP models.…”
Section: The Research Contextmentioning
confidence: 99%
See 3 more Smart Citations